Faire du terrain dans l’Égypte révolutionnaire - Lise Debout; Gaëtan Du Roy; Clément Steuer (Revue des Mondes Musulmans et de la Méditerranée)
This article offers a reflection of three young researchers – an urbanist, an historian and a political scientist – on the impact of the Egyptian revolution in carrying out their fieldwork research. Looking retrospectively at their research activities during a crucial year, 2011, they question not only the disruptive events taking place among the people they were studying, but also their own relationship with these people and their environment. Even though belonging to three very different fields of the social sciences, in terms of the material used and the scale of analysis, the revolutionary events led the three researchers to very similar methodological approaches, converging towards a more «  micro  » perspective on their respective topics. Finally, this «  bottom-up  » approach – which tends to cross over the temporal, spatial and political dimensions of the studied phenomena – proved to be very relevant in analyzing the dynamics of power among different sectors of society.